A heparin‐mimicking reverse thermal gel for controlled delivery of positively charged proteins. Issue 6 (21st October 2014) - Peña, Brisa; Shandas, Robin; Park, Daewon
Abstract Positively charged therapeutic proteins have been used extensively for biomedical applications. However, the safety and efficacy of proteins are mostly limited by their physical and chemical instability and short half‐lives in physiological conditions. To this end, we created a heparin‐mimicking sulfonated reverse thermal gel as a novel protein delivery system by sulfonation of a graft copolymer, poly(serinol hexamethylene urea)‐co‐poly(N‐isopropylacylamide), or PSHU‐NIPAAm. The net charge of the sulfonated PSHU‐NIPAAm was negative due to the presence of sulfonate groups. The sulfonated PSHU‐NIPAAm showed a typical temperature‐dependent sol‐gel phase transition, where polymer solutions turned to a physical gel at around 32°C and maintained gel status at body temperature. Both in vitro cytotoxicity tests using C2C12 myoblast cells and in vivo cytotoxicity tests by subcutaneous injections demonstrated excellent biocompatibility. In vitro release tests using bovine serum albumin revealed that the release from the sulfonated PSHU‐NIPAAm was more sustained than that from the plain PSHU‐NIPAAm. Furthermore, this sulfonated PSHU‐NIPAAm system did not affect protein structure after 70‐day observation periods. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 2102–2108, 2015.